2018
DOI: 10.1302/0301-620x.100b1.bjj-2017-0548.r1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the hip after resection of periacetabular oncological lesions

Abstract: Both the rate of complications and mortality are high following resection of oncological periacetabular lesions and reconstruction. Many types of reconstruction have been used with unique challenges and complications for each technique. Newer prostheses, including custom-made prostheses and porous tantalum implants and augments, have shown promising early functional and radiographic outcomes. Cite this article: 2018;100-B(1 Supple A):22-30.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 67 publications
0
67
1
3
Order By: Relevance
“…A systematic study has shown that complications of these surgical procedures, including deep infection, dislocation, nonunion of bone graft, and fracture, have a total incidence of up to 50%, among which deep infection and dislocation are the most common [ 17 ]. These complications are closely related to the large number of bone defects and soft tissue injuries caused by tumor resection [ 18 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic study has shown that complications of these surgical procedures, including deep infection, dislocation, nonunion of bone graft, and fracture, have a total incidence of up to 50%, among which deep infection and dislocation are the most common [ 17 ]. These complications are closely related to the large number of bone defects and soft tissue injuries caused by tumor resection [ 18 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Post-surgical infection following spine surgery occurs in 1% to 14% of patients, depending on the preoperative diagnosis and type of surgery; 14,15 similar figures are reported for a variety of surgical procedures involving implantable devices in orthopaedics and trauma. 16-18…”
Section: The Impact Of Implant-related Infections In Orthopaedics Andmentioning
confidence: 99%
“…Total Hip Arthroplasty (THA) is considered an effective treatment to improve the function of hip joint failure caused by: arthritis [1] (including osteoarthritis, rheumatoid arthritis, traumatic arthritis, and arthritis caused by other reasons, e.g., the microbleeds in joint capsule of congenital afibrinogenemia patients [2]), fractures [3], malignant bone tumors [4], and so on. However, the main complication of THA, aseptic loosening [5], has plagued both patients and clinicians for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Medial-Lateral; 2 Cranial-Caudal;3 Anterior-Posterior;4 Marker-based RSA; "poorly" reliability (ICC < 0.40) was marked in bold.…”
mentioning
confidence: 99%